“Bridge over the Precipice”? Bohdan Zynoviy Khmelnytskyi by Mykola Mashchenko Compared to With Fire and Sword by Jerzy Hoffman - Podlyuk, Anastasiya (Slavia Orientalis, 2020)
The film Bohdan Zynoviy Khmelnytsky by the Ukrainian director Mykola Mashchenko is little‑known in Poland. The director intended it to become a “bridge over the precipice” which divides both nations, but from the very beginning it was negatively perceived both by the audience and critics. The Ukrainian reception of Jerzy Hoffman’s With Fire and Sword, a movie referring to the same events from a common past, seems to be completely different entity. The work by the Polish artist remains of interest even twenty years after its release. The article is an attempt to determine the reasons for this situation. The author analyzes the artistic values of Mashchenko’s film, the characters’ performances and historiosophy, and, comparing those with Hoffman’s screening, looks for an answer to the question as to the motives for the contrasting reception of these films by Ukrainian society.
Keywords: historical film; 'With Fire and Sword'; Jerzy Hoffman; 'Bohdan Zynoviy Khmelnytsky'; Mykola Mashchenko